2023
DOI: 10.2147/ndt.s362202
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Acute-Onset Neuropsychiatric Syndrome: Current Perspectives

Abstract: Pediatric acute-onset neuropsychiatric syndrome (PANS) features a heterogeneous constellation of acute obsessive-compulsive disorder (OCD), eating restriction, cognitive, behavioral and/or affective symptoms, often followed by a chronic course with cognitive deterioration. An immune-mediated etiology is advocated in which the CNS is hit by different pathogen-driven (auto)immune responses. This narrative review focused on recent clinical (ie, diagnostic criteria, pre-existing neurodevelopmental disorders, neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 198 publications
0
7
0
Order By: Relevance
“…Similarly, children and adolescents with Tourette syndrome may be more likely to have GABHS infections and exhibit more antibacterial and antineuronal antibodies with a stronger immune response to GABHS [24,39]. Notably, Snider et al [38] concluded that antibiotic therapy with azithromycin and penicillin in children with PANDAS is effective in preventing GABHS infections and GABHS-related psychiatric exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, children and adolescents with Tourette syndrome may be more likely to have GABHS infections and exhibit more antibacterial and antineuronal antibodies with a stronger immune response to GABHS [24,39]. Notably, Snider et al [38] concluded that antibiotic therapy with azithromycin and penicillin in children with PANDAS is effective in preventing GABHS infections and GABHS-related psychiatric exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…We did not include animal studies in our analysis, as they replicate OCD models and are predominantly based on serotonergic and dopaminergic systems (Alonso et al, 2015;Grados et al, 2016). This topic of inflammation in OCD and associated disorders has also been the subject of recent reviews (Bhatt et al, 2023;Gagliano et al, 2023;Kamble & Dandekar, 2023;Marazziti et al, 2023;Vreeland et al, 2023), underscoring its relevance and the ongoing discourse in the scientific community.…”
Section: Infl Ammati On In O CDmentioning
confidence: 99%
“…Some authors advocate for PANDAS belonging to the complex Pediatric Acute-Onset Neuropsychiatric Syndrome (PANS) spectrum, assuming that not only GAS may induce neuropsychiatric symptoms in children. However, this point is also debatable, and different classification criteria have been provided for PANS patients, making this aspect even more complex [13]. According to the latest accredited evidence, after a GAS infection, antibodies produced against GAS epitopes presumably cross-react against self-tissue, such as proteins expressed in the neurons of basal ganglia, through a molecular mimicry mechanism, suggesting an autoimmune pathogenesis similar to SC [14].…”
Section: Pathophysiologymentioning
confidence: 99%